Effect of Formaldehyde to Phenol Ratio in Phenolic Beads on Pore Structure, Adsorption and Mechanical Properties of Activated Carbon Spheres - Singh, Arjun; Aggrawal, Sanjeevan; Lal, Darshan (Defence Science Journal, 2019)
Phenolic beads (PBs) prepared from different formaldehyde to phenol (F/P) molar ratios were used as polymeric precursor for activated carbon. Activated carbon spheres (ACSs) have been produced from PBs via the physical activation process using carbon dioxide (CO2) as activating agent at 950 °C for different burn-off. The prepared ACSs were investigated for nitrogen adsorption, surface morphology and compressive strength by means of BET surface area analyser, scanning electron microscopy (SEM) and carbon and sphere tester techniques. The results indicated that the effects of F/P ratio observed, especially variation in the adsorption and mechanical properties. It was found that ACSs obtained from F/P ratio one showed the superior adsorption properties, possessed a high BET surface area in a range of 836 m2 g-1 to 3694 m2 g-1 with high pore volume (0.47 cm3 g-1 - 2.47 cm3 g-1) and 73-97 per cent microporosity. The BET surface area and pore volume increased, while the microporosity gradually decreased, with increasing the extent of burn-off. Compressive strength decreased with increasing F/P ratio as well as the extent of burn-off. ACSs upheld improved compressive strength (from 160 N mm-2 to 9 N mm-2) than those obtained from F/P ratio 2 and 3 in PBs. SEM studies of ACSs demonstrated well developed pore structure.